2016
DOI: 10.1007/s13402-015-0261-5
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma associated antigen (MAGE)-A3 promotes cell proliferation and chemotherapeutic drug resistance in gastric cancer

Abstract: From our results we conclude that MAGE-A3 expression is regulated epigenetically by promoter methylation, and that its expression contributes to gastric cell proliferation and drug sensitivity. This study underscores the potential implications of MAGE-A3 as a therapeutic target and prognostic marker in gastric cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
5
14
0
Order By: Relevance
“…p53 is well-known for its role as the guardian of the genome. It also plays a pivotal role in suppressing tumorigenesis (43). Our experimental data demonstrate that two p53-dependent pathways play pivotal roles in this process, as shown in Fig.…”
Section: Discussionsupporting
confidence: 65%
“…p53 is well-known for its role as the guardian of the genome. It also plays a pivotal role in suppressing tumorigenesis (43). Our experimental data demonstrate that two p53-dependent pathways play pivotal roles in this process, as shown in Fig.…”
Section: Discussionsupporting
confidence: 65%
“…In investigating this process, we focused on MAGE‐A3, a member of tumor‐testis antigens family. MAGE‐A3 is an emerging prognostic factor for GC and is likely a marker for the early diagnosis and micrometastasis identification of GC 21,22 . In this study, we also verified that MAGE‐A3 was closely related with poor prognosis of GC.…”
Section: Discussionsupporting
confidence: 77%
“…Melanoma‐associated antigen‐A3 is over‐expressed in many malignant tumors (eg, colorectal and liver cancer) and has a high degree of specificity, especially in GC, with the positive expression rate up to 40% 21 . The current researches on MAGE‐A3 indicate that MAGE‐A3 can promote tumor cell proliferation and affect tumor prognosis by regulating multiple apoptotic proteins 22 . Thus, we hypothesized that YAP/MAGE‐A3 may be a new target for sitagliptin.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The expression of several MAGE subgroups is correlated with poor prognosis and chemotherapeutic resistance. 14 It was reported that MAGE-A11 is an independent poor prognostic marker for esophageal squamous cell carcinoma (ESCC). 15 And frequently expressed in breast cancer which is associated with poor prognosis as well.…”
Section: Introductionmentioning
confidence: 99%